2009
DOI: 10.1128/aem.01371-08
|View full text |Cite
|
Sign up to set email alerts
|

Type II Thioesterase ScoT, Associated with Streptomyces coelicolor A3(2) Modular Polyketide Synthase Cpk, Hydrolyzes Acyl Residues and Has a Preference for Propionate

Abstract: Type II thioesterases (TE IIs) were shown to maintain the efficiency of polyketide synthases (PKSs) by removing acyl residues blocking extension modules. However, the substrate specificity and kinetic parameters of these enzymes differ, which may have significant consequences when they are included in engineered hybrid systems for the production of novel compounds. Here we show that thioesterase ScoT associated with polyketide synthase Cpk from Streptomyces coelicolor A3(2) is able to hydrolyze acetyl, propion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…This contrasts with the TE domain of the lasalocid PKS, which clades with typical type I TEs. Based on the literature precedent, [17,19] AjuTE would be expected to show a preference in the deacylation reaction for short acyl chains such as acetate and propionate, consistent with its role in removing aberrant acyl units from the carrier-protein domains. As TEIIs are encoded by discrete genes, the in silico analysis also raised the possibility that the ajuTE gene had once been a stand-alone element, but had become fused genetically to the end of gene ajuH.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This contrasts with the TE domain of the lasalocid PKS, which clades with typical type I TEs. Based on the literature precedent, [17,19] AjuTE would be expected to show a preference in the deacylation reaction for short acyl chains such as acetate and propionate, consistent with its role in removing aberrant acyl units from the carrier-protein domains. As TEIIs are encoded by discrete genes, the in silico analysis also raised the possibility that the ajuTE gene had once been a stand-alone element, but had become fused genetically to the end of gene ajuH.…”
Section: Discussionmentioning
confidence: 78%
“…acylation of the acyl-enzyme intermediate has been shown to be the rate-determining step in turnover of the p-NP esters by both type I and II TEs. [17,19,35] As this is the stage at which the isochromanone ring would be formed in the normal pathway, it was of particular interest to characterize TE substrate specificity during this half of the reaction. One disadvantage of using these esters, however, is that substrate-saturating conditions cannot be attained due to their poor aqueous solubility, and therefore it is not possible to determine apparent k cat and K M values.…”
Section: Expression Purification and Kinetic Analysis Of A Panel Of mentioning
confidence: 99%
See 1 more Smart Citation
“…As the yields of the polyketide and polypeptide products were often considerably impaired in the knock-out mutants, type II thioesterases were proposed to restore the acyl or peptidyl carrier protein function by releasing undesirable intermediates, resulting from a priming or processing error (51)(52)(53)(54). The asuC15 mutant produced a normal amount of asukamycin A1, yet the yield of the congeners A2-A7 was significantly reduced (Fig.…”
Section: Oxygenation Of Protoasukamycin-s Parvulus Tü 64 Fermentatiomentioning
confidence: 99%
“…BLAST analysis indicated that ChlK is a type II thioesterase, which probably removes aberrantly loaded substrates from the polyketide chain to promote the specific loading efficiency (28,29). Both HPLC analysis and bioassays showed that the CHL production in ⌬chlK was distinctly lower than that in wild type and was almost fully restored in the complementary strain (⌬chlK/pLY108).…”
Section: Identification Of the Target Genes Of Chlf1 And Its Bindingmentioning
confidence: 99%